Workers' Trust Funds and the Logic of Wage Profiles - Akerlof, George A.; Katz, Lawrence F. (Quarterly Journal of Economics, 1989)
This paper defines a concept, a worker's trust fund, which is useful in analyzing optimal age-earnings profiles. The trust fund represents what a worker loses if dismissed from a job for shirking. In considering whether to work or shirk, a worker weighs the potential loss due to forfeiture of the trust fund if caught shirking against the benefits from reduced effort. This concept is used to show that the implicit bonding in upward sloping age-earnings profiles is not a perfect substitute for an explicit up-front performance bond (or employment fee). It is also shown that the second-best optimal earnings profile in the absence of an up-front employment fee pays total compensation in excess of market clearing in a variety of stylized cases.